PENINGKATAN KESADARAN MASYARAKAT : MEMAHAMI KEHIDUPAN DAN TANTANGAN ANAK-ANAK BERKEBUTUHAN KHUSUS - Opi Andriani; Azzura Della Rinjani; Mutiya; Putri Aprilia (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Community knowledge about the Rights of Children with Special Needs (ABK) and public awareness to help ABK parents in meeting the needs of their children, ABK parents have a great challenge in caring for and meeting the needs of their children. Ideally, this parental responsibility needs help and support from the community to create a comfortable atmosphere and help so that ABK can develop optimally. However, often ABK receives violence and exclusion from the surrounding community. The purpose of this study is to describe knowledge about ABK Rights and public awareness about ABK. The results showed that people do not know much about how to behave and treat ABK and their parents. In addition, there are still ABK parents who have not been able to take advantage of access to health services and education provided by the government because they feel embarrassed to bring their children to mix with other communities. Socialization and counseling on the handling of ABK have been carried out by the government, but the community thinks that this activity is only important to be attended by ABK parents. The implementation of socialization and counseling needs to be carried out from the smallest government unit at the village level, namely RT so that public knowledge and awareness can increase.